Diplomatic Alliance Procession Between Elizabeth I with Murad III Amidst European Tensions (1583-1603) - Hadi, Muhammad Sholikhul Hadi (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2025)
Abstract:  A unique diplomatic alliance once existed between the Tudor Kingdom of England under the leadership of Queen Elizabeth I, a Protestant, and the Ottoman Empire under the leadership of Sultan Murad III, a Muslim, at the end of the 16th century AD. This alliance was a mutually beneficial relationship between two nations that emerged amid religious and political tensions in Europe, following Queen Elizabeth I's excommunication from the European Catholic Church by Pope Pius V through the papal bull, Regnan in Excelsis, for converting her kingdom's ideology to Protestantism. In a situation of isolation and threat from Catholic powers, particularly King Philip II of Spain, Queen Elizabeth I instead forged a strategic partnership with the largest Islamic power at the time, the Ottoman Empire, to weaken Catholic hegemony in Europe. This study highlights the alliance process between Queen Elizabeth I and Sultan Murad III amid religious and political tensions throughout Europe using an international relations approach, the concept of diplomatic alliance, and Hans J. Morgenthau's theory of realism. The research method employed is historical research, which consists of heuristics (source collection), verification (source criticism), interpretation (source analysis), and historiography (historical writing). The findings of this study describe that the diplomatic alliance process officially began in 1583 AD, with the dispatch of William Harborne as the official British ambassador to Constantinople to obtain special privileges from Turkey. This relationship also aimed to weaken European Catholic hegemony, open trade routes through capitulation, and establish a network of British consuls in Turkish territory. This diplomatic alliance between two ideologically distinct worlds was pragmatic and flexible, yet it was shaped by dynamics arising from changes in British ambassadors, diplomatic competition, and internal political shifts in Turkey.   Abstrak: Hubungan Aliansi diplomatik yang unik pernah terjalin antara Kerajaan Tudor Inggris di bawah kepemimpinan Ratu Elizabeth I, seorang Protestan, dengan Kesultanan Turki Utsmani di bawah kepemimpinan Sultan Murad III, seorang muslim pada akhir abad ke-16 M. Aliansi ini merupakan hubungan mutualistik antara dua negara yang terjadi di tengah ketegangan agama dan politik di Benua Eropa, setelah Ratu Elizabeth I mengalami pengucilan dari Gereja Katolik Eropa oleh Paus Pius V melalui bulla kepausan, Regnan in Excelsis, karena mengubah ideologi kerajaannya menjadi Protestan. Dalam situasi isolasi dan ancaman dari kekuatan Katolik, terutama dari Raja Philip II dari Spanyol, Ratu Elizabeth I justru menjalin kerja sama strategis dengan kekuatan Islam terbesar saat itu, Kesultanan Turki, guna melemahkan hegemoni Katolik di Eropa. Penelitian ini menyoroti proses aliansi yang terjadi antara Ratu Elizabeth I dengan Sultan Murad III di tengah gejolak ketegangan agama dan politik di seluruh Eropa dengan menggunakan pendekatan hubungan internasional, konsep aliansi diplomatik, serta teori realisme oleh Hans J. Morgenthau. Sedangkan untuk metode penelitiannya menggunakan metode penelitian sejarah yang terdiri dari heuristik (pengumpulan sumber), verifikasi (kritik sumber), interpretasi (penafsiran sumber), dan historiografi (penulisan sejarah). Temuan dalam penelitian ini menggambarkan bahwa prosesi aliansi diplomatik dimulai secara resmi pada tahun 1583 M, dengan mengirim William Harborne sebagai duta besar resmi Inggris ke Konstantinopel, guna memperoleh hak istimewa dari Turki. hubungan ini juga bertujuan melemahkan hegemoni Katolik eropa, membuka jalur perdagangan lewat kapitulasi, dan membentuk jaringan konsul Inggris di wilayah Turki. Aliansi diplomatik antara dua dunia ideologi yang berbeda ini, bersifat pragmatis dan fleksibel, namun diwarnai dinamika akibat pergantian duta Inggris, persaingan diplomatik, dan perubahan politik internal Turki.